Design, Culture and Visuality - Ezequiel, Helena de Barros; Pires e Castro, Barbara; Geiger, Noni; Martins, Marcos André Franco; da Fonseca Neto, Almir Mirabeau; de Niemeyer, Lucy Carlinda da Rocha (DAT Journal, 2024)
The article presents the research area of Design, Culture and Visuality, proposed in 2024 as part of the reformulation of the Graduate Program in Design of the Design School of the State University of Rio de Janeiro. This research field of Design brings together studies that reflect on different manifestations of visuality and image technologies, as well as the relationship between design and history and material culture; it investigates visual and performing arts, material and digital technologies, moving image processes, printing processes, typography, data visualization, artificial intelligence, media and interfaces. It focuses on investigations into audiovisual expressions of academic research, design, art and media: discourses and practices, art, aesthetic experience, data and technology, history and graphic memory. It seeks to establish connections between these manifestations, communication processes and their social impact. It also addresses investigations into writing, the archive, the relationship between text and image and the dynamics of contemporary media.